MENINGKATKAN MINAT BACA DAN KEMAMPUAN BAHASA INGGRIS ANAK MELALUI PEMBENTUKAN RUMAH BACA â€œENGLISH EXTENSIVE READINGâ€ - Wida Mulyanti; Lystiana Nurhayat Hakim (Journal of Empowerment Community, 2021)
This community service is an English language learning program for elementary school-aged children in Kampung Cantilan, Desa Sukarame. This program is organized based on requests from parents who report that they want their children to learn English, but since Kurikulum 2013 (K-13) has been implemented, English is not taught in Elementary School. It does not belong to primary time allocation where it depends on the school policy to take English as an extracurricular subject or not. After conducting the interviews, it can be concluded that the parents want their children to learn English and the children have high motivation to learn English but lack of interest in reading books. Hence, this program is conducted as a means for children to get access to learn English and to get motivated to read a lot. The method used in this community service program was adapted from Vincent II (2009), namely community development practice, whereas the steps used in providing training materials are: orientation, training, feedback and continuation. Pre-test and post-test are carried out at the beginning and at the end of the program and show an increase in scores from pre-test to post-test. From the test results, it can be concluded that this service contributes in gaining children’s English language ability. Whereas from the interviews, it is known that the children's interest in reading has increased.